Онтологизация как необходимая теоретическая процедура в исследовании этнических процессов - Ємельянова, Юлія Павлівна; Емельянова, Юлия Павловна; Yemelianova, Yuliia P. (Національна академія наук України, 2012)
В статье рассматривается возможная стратегия исследования этнических процессов. Обосновывается необходимость логико-философского обобщения массива знаний по этому вопросу, накопленных в науке о человеке и его жизнедеятельности.

The possible strategy of ethnical processes' research is examined in this article. The necessity of logical-philosophical generalization of the knowledge array about the human being and their vital activity, accumulated by science, is granted here.
Ontologization as an essential theoretical procedure in ethnical processes' research
Keywords: социальная реальность; природа человека; становление; этничность; культура; social reality; human nature; formation (establishment, making); ethnicity; culture